Impact of Entrepreneurial Identity Aspiration and Self-Efficacy towards Entrepreneurial Behavior of the Working Class of Davao City - de Gracia, Daisy Vale Avila; Campos, Karl P. (Journal of Economics Education and Entrepreneurship, 2023)
This study aims to quantify and measure the relationship of Entrepreneurial Identity Aspiration and Self-Efficacy to Entrepreneurial Behavior of the working class of Davao City where the culture has strong emphasis on working and providing for the family. The data is collected from 150 working people in Davao City through the e-questionnaires using Snowball sampling. Using a correlation-descriptive research design and multiple linear regression technique, the undertaking reveals that both Entrepreneurial Identity Aspiration and Self-Efficacy have a statistically significant impact on Entrepreneurial Behavior. However, the study also identified that Self-efficacy has a higher degree of correlation and effect towards Entrepreneurial Behavior. Furthermore, the results on Entrepreneurial Identity Aspiration show different results compared to relative studies presented. The results assume that even with the desire and aspiration to take an entrepreneurial role in the future, a person who is lacking on self-efficacy will not engage on entrepreneurial activities.